U.S. Lawsuits about religious institutions and their members (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
The purpose of this study is twofold. In one hand, it exposes how to recognize thelegal personality and capacity to act in the American Common Law to qualified religioussubjects (religious ministers and organizations). On the other hand, it explains which are the main lawsuits and proceedings for these kinds of subjects, and what itis the usual responsibility for those trials.
Keywords: The United States of America (US/USA); Legal System & Lawsuit; religious factor; clergy; religious organizations/institutions; trials and proceedings.